NOTA SOBRE AS EXIGÃŠNCIAS MINERAIS DA PIMENTA MALAGUETA (Capsicum frutescens) - Malavolta, E.; Malavolta, M. L.; Cabral, C. P.; Carvalho, M. J. R. de (REVISTA DE AGRICULTURA, 2015)
NOTA SOBRE AS EXIGÃŠNCIAS MINERAIS DA PIMENTA MALAGUETA (Capsicum frutescens)